Design Of Alternative Power Plant With Apply Flywheel Energy Storage System - Ferdian A V (Bandar Lampung University (UBL), 2017)
Any design or concept of energy generating devices must be in accordance with the laws applicable in the fields of physics, one of which is the law of conservation of energy. This study aimed to determine whether this power plant can work with good efficiency. In the design of the power plant is used a 36 volt DC electric motor to rotate a flywheel (flywheel) and a 3000 watt generator with a series-v belt transmission. Initial power to drive the electric motor comes from the battery. Then the power output of the generator used to charge the battery back and the rest is used for other purposes (load). The result is anpoweroutputof the generator is smaller thanpowerthe input by the electric motor, so that the plant can not be used in a long time.The small plant efficiency is due to several factors diantarannya generator and electric motor efficiency is low and the battery charging load is too large so there is a balance between charging and konsunsi power by the electric motor